WHY DOES SURGICAL INFECTION OFTEN AFFECT DIABETICS? : Literature review of recent data - Babadjanov, B.D.; Okhunov, A.O.; Atakov, S.S.; Kasimov, U.K.; Sattarov, I.S.; Matmuratov, K.J.; Bobobekov, A.R.; Khudaybergenova, N.Sh.; Khamdamov, Sh.A.; Bobokulova, Sh.A.; Boboyev, K.Kh.; Abdurakhmanov, F.M.; et al. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The review article is devoted to the problem of the relationship between diabetes mellitus and surgical infection. It is known that patients with diabetes mellitus are most susceptible to the development of surgical infection. Moreover, the infectious process can affect both soft tissues and internal organs. And any process in patients with diabetes mellitus associated with a surgical infection proceeds especially, aggressively, and requires an individual approach that goes beyond the approved standards. However, until now Issues related to the causes and consequences of such a medical phenomenon as surgical infection in patients with diabetes mellitus remain controversial. Giving a review of the literature, we tried to draw a line on these controversial issues and identify specific areas that are important from the point of view of the characteristics of the pathogenesis of the onset and course of the disease. We hope that this review, enriched with modern literature sources, will allow researchers to look at this problem through the realities that occur in clinical practice.